What retrofits could make classroom environments more conducive to learning? - Villavicencio, Xuzel; Toyinbo, Oluyemi (2023)
This slide deck relates to a presentation given by OpenDevEd at The Education and Development Forum in Oxford (UKFIET 2023), as part of the sub-theme “Conflict, crisis, climate, and migration”. This presentation was part of the symposium called Climate, environment and education outcomes – Preliminary findings and practical experience from East and West Africa.